2017
DOI: 10.1371/journal.pone.0169601
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Intestinal Iron Absorption Using Genetic Programming

Abstract: Iron is a trace metal, key for the development of living organisms. Its absorption process is complex and highly regulated at the transcriptional, translational and systemic levels. Recently, the internalization of the DMT1 transporter has been proposed as an additional regulatory mechanism at the intestinal level, associated to the mucosal block phenomenon. The short-term effect of iron exposure in apical uptake and initial absorption rates was studied in Caco-2 cells at different apical iron concentrations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Uptake was considered as the total radioactivity in the cells plus the basolateral medium after incubation. Fe–ascorbate was used to avoid a possible interference of Dcytb ferrireductase with the uptake process [49].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Uptake was considered as the total radioactivity in the cells plus the basolateral medium after incubation. Fe–ascorbate was used to avoid a possible interference of Dcytb ferrireductase with the uptake process [49].…”
Section: Methodsmentioning
confidence: 99%
“…Experimental data for the second challenge were used for phenomenologically validating the proposed model. We presented a detailed description of the application of the Jackknife method in [49]. It has been shown that the coefficient of determination R 2 is an inadequate measure for the goodness of fit in non-linear models, since differences in model quality rarely affect its value more than in the third to fifth decimal place [78].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the cytosol, iron is neutralized by ferritin (a multimeric iron-storage protein) (Table I) and weakly bound together to form a pool of iron termed the cytoplasmic labile iron pool (cLIP) (20). The cLIP supplies iron to a number of cytoplasmic enzymes, in addition to mitochondria for heme and iron sulfur cluster synthesis.…”
Section: Iron Absorptionmentioning
confidence: 99%